2018
DOI: 10.1093/cid/ciy274
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial of the Quadrivalent Human Papillomavirus Vaccine in Human Immunodeficiency Virus-Infected Adults Aged 27 Years or Older: AIDS Clinical Trials Group Protocol A5298

Abstract: NCT01461096.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(155 citation statements)
references
References 34 publications
3
148
1
3
Order By: Relevance
“…As regards HAART, no evidence is currently available that it may play a role in the clearance of HPV infection, in the control of precursor anogenital cancer lesions or in the possible regression of previous high-grade lesions [67]. Moreover, the role of HPV vaccination was not supported by a trial on the prevention of new anal HPV infections and on the outcomes of high-grade anal lesions, conducted in HIVinfected adults [68].…”
Section: Viral Co-infectionsmentioning
confidence: 99%
“…As regards HAART, no evidence is currently available that it may play a role in the clearance of HPV infection, in the control of precursor anogenital cancer lesions or in the possible regression of previous high-grade lesions [67]. Moreover, the role of HPV vaccination was not supported by a trial on the prevention of new anal HPV infections and on the outcomes of high-grade anal lesions, conducted in HIVinfected adults [68].…”
Section: Viral Co-infectionsmentioning
confidence: 99%
“…Good efficacy could be shown for cervical and vulvar neoplasia [58]. However, a recent phase III trial suggested low efficacy for the prevention of HPV infection and HGAIN development in HIV-positive individuals [59]. Altogether, evidence for the discussed treatment options is insufficient, and many small series revealed low efficacy.…”
Section: Treatment Of Ainmentioning
confidence: 99%
“…EA has been shown to be superior to topical immune modulators or chemotherapeutics for the treatment of anal HSIL . In a retrospective study, adding HPV vaccination to HSIL treatment (adjuvant HPV vaccination) improved treatment outcomes among HIV‐uninfected MSM and a mathematical modeling study found adjuvant vaccination to be cost‐effective; however, a recent randomized clinical trial did not confirm such synergy among PLWH …”
Section: Introductionmentioning
confidence: 99%
“…15 In a retrospective study, adding HPV vaccination to HSIL treatment (adjuvant HPV vaccination) improved treatment outcomes among HIV-uninfected MSM and a mathematical Cancer April 1, 2020 modeling study found adjuvant vaccination to be cost-effective 16,17 ; however, a recent randomized clinical trial did not confirm such synergy among PLWH. 18 Studies regarding ablation efficacy have been heterogeneous with regard to cohort characteristics and surveillance strategies, yet HSIL clearance after infrared coagulation (IRC) and/or EA has been consistently high, ranging from 53% to 87% in HIV-infected and HIVuninfected MSM. [19][20][21][22][23][24] However, HSIL recurs frequently after ablation and necessitates ongoing surveillance and repeated treatments.…”
Section: Introductionmentioning
confidence: 99%